A Semi-Analytical Study on the Magnetohydrodynamic Flow of Casson Nanofluid - Kalaivani, M.; Ananthaswamy, V.; Sivasankari, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
The Magnetohydrodynamic Casson nanofluid with heat radiation is evaluated mathematically across an elongating or shrinking sheet within a porous substance exhibiting brownian and thermophoretic diffusion. By incorporating non-dimensional variables in the formulation, the controlling equations acquire dimensionless. The approximate analytical approach (ASM) and Modified Homotopy Analysis Methodology (MHAM) are utilized to attain the velocity, temperature and concentration explicitly in a dimensionless manner. We graphically portray the model’s physical components to interpret their consequences. Furthermore, the semi-analytical expressions for the Sherwood number, Nusselt number, and dimensionless skin friction factor are assessed. Comparing the semi-analytical results with the numerical results, a great fit is confirmed.